The effect of horse velocity on the output of an inertial sensor system - Moorman, V. J.; Frisbie, D. D.; Kawcak, C. E.; McIlwraith, C. W. (Journal of Equine Veterinary Science, 2017)
Highlights: •Horse trotting velocity has a significant effect on stride rate. •Trotting velocity did not have a significant effect on objective forelimb lameness. •Trotting velocity had a small but significant effect on objective hindlimb lameness.